(untitled) (Journal of Hama University, 2022)
Introduction: Border molding is one of the most important steps that a clinician performs in the process of fabricating complete dentures that affect to the retention of the complete dentures and can be achieved with several techniques that have striven to improve the retention and stability of patients’ dentures Aim of the Study: comparative the retention of complete dentures bases between the border molding technique using Light-Cured Acrylic Resin in single step and the sectional border molding technique using low fusing impression compound. Materials and methods: The sample consisted of twelve healthy completely edentulous patients, (average of 45-65 years of age). Borders were molded using Light-Cured Acrylic Resin in single-step and the sectional technique using low fusing impression compound. The two techniques followed by a final impression using zinc oxide-eugenol impression paste, then a digital force meter was used to measure retention strength provided by each technique. The data obtained was statistically analyzed using Student’s independent T-test, Pearson Correlation Coefficient. The level of confidence was set at 95%. Results: the statistical analysis showed no significant difference in bases retention between the two border molding techniques. Conclusion: within the limits of this study it can be concluded that single step border molding using Light-Cured Acrylic Resin provided similar clinical retention on denture bases compared to sectional border molding using low fusing impression compound